Polyelectrolyte Complex (PEC) of the Alginate-Chitosan Membrane for Immobilizing Urease - Dhony Hermanto; Mudasir Mudasir; Dwi Siswanta; Bambang Kuswandi; Nurul Ismillayli (Journal of Mathematical and Fundamental Sciences, 2019)
PEC of the alginate-chitosan membrane as supporting material for immobilizing urease was produced. This study aimed to develop a supporting material for enzyme immobilization that has high stability, a fast response time and an easy and relatively inexpensive preparation procedure. An alginate-chitosan PEC membrane was produced by reacting alginate hydrosol and chitosan (1:1 in mass) at pH 5.28, followed by mixing and drying at room temperature. The FTIR spectra, XRD patterns and SEM assay confirmed that alginate-chitosan PEC was obtained. The color change of the BTB indicator proved that urease was trapped in the cavities of the alginate-chitosan PEC membrane while the immobilized urease still showed catalytic activity. Thus, the membrane of alginate-chitosan PEC has good characteristics as a matrix for urease immobilization.